Analysis of Bacterial DNA from Bioreactor Effluent Samples for Hydrogen Production by Dark Fermentation - Gupta, Soumya; Salafranca, Jesús; Grasa, Laura; Fernandes, Annabel (Jornada de Jóvenes Investigadores del I3A, 2024)
Hydrogen (H2) production from biomass using bacteria is a cost-effective approach. The bacterial DNA from effluent samples were extracted, amplified and analysed, and taxonomic trees of all the species present were obtained. HRTs and synthetic matrix influenced bacterial growth. Clostridium butyricum was prominent in the samples indicating its versatile growth conditions.